2016
DOI: 10.1038/ng.3542
|View full text |Cite|
|
Sign up to set email alerts
|

Cis-regulatory architecture of a brain signaling center predates the origin of chordates

Abstract: Genomic approaches have predicted hundreds of thousands of tissue specific cis-regulatory sequences, but the determinants critical to their function and evolutionary history are mostly unknown1–4. Here, we systematically decode a set of brain enhancers active in the zona limitans intrathalamica (zli), a signaling center essential for vertebrate forebrain development via the secreted morphogen, Sonic hedgehog (Shh)5,6. We apply a de novo motif analysis tool to identify six position-independent sequence motifs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 55 publications
1
73
0
Order By: Relevance
“…Others have been identified through genetics in mouse and man when mutations in Shh enhancers cause phenotypes that result from aberrant control of specific aspects of Shh expression in development. Most recently, information on transcription factor motifs in known Shh brain enhancers has been used to search for other similar patterns of motifs in the Shh regulatory domain and has identified a new enhancer that drives Shh expression in a discrete region of the brain [7,13]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have been identified through genetics in mouse and man when mutations in Shh enhancers cause phenotypes that result from aberrant control of specific aspects of Shh expression in development. Most recently, information on transcription factor motifs in known Shh brain enhancers has been used to search for other similar patterns of motifs in the Shh regulatory domain and has identified a new enhancer that drives Shh expression in a discrete region of the brain [7,13]. …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, ENCODE and Roadmap data also indicate that this region of the mammalian genome has active enhancer chromatin marks in neural tissue, as well as in the liver (figure 6 a ; electronic supplementary material, figure S3) and gastric tissue (figure 6 b ). Important sequences required for enhancer function work as assemblies of transcription factor motifs [13]. SBE6.1 and SLGE motifs may be intermingled but still specific to a precise tissue and stage of development, or may be overlapping to various extents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Barhl2 expression begins at E10.5 in the developing diencephalon and expression of Shh begins at E9 in the ZLI [29], it is likely that loss of Barhl2 restricts the dorsal expansion of ZLI. Recently published studies have identified a Shh ZLI enhancer of evolutionary origin and have demonstrated that BARHL2 directly binds to this enhancer in E10.5 mouse embryo brains [30]. Moreover, studies in Xenopus have shown that Barhl2 restricts the dorsal expansion of the ZLI by affecting the competence of neuroepithelial cells to respond to the secreted form of SHH from the alar plate [31].…”
Section: Discussionmentioning
confidence: 99%
“…TAD conservation could thus reveal deep homology of entire regulatory landscapes, just as deep conservation of enhancer activities might inform us about evolutionary relationships of different morphological structures that they help to pattern [76]. Clearly, however, the most instructive insights at the gene regulatory level would come from the integration of different NGS technologies to first describe the regulatory architecture at loci of interest, and then test them in reciprocal, cross-species enhancer reporter experiments [83][84][85].…”
Section: Homology Assessment: Gene Expression and Regulatory Strategiesmentioning
confidence: 99%